On psychological principles of the formation of academic groups at higher schools - Kabašinskienė, R. (Psichologija, 1988)
The paper deals with the problem on the developmental process of the personality’s professional self-determination. Special attention is attached to the moment of the choice of profession by secondary school graduates and to the period of higher professional training. The influence of the academic group upon the formation of occupational self-determination of the future professionals’ personality, and especially upon his professional interests, is pointed out.